2006
DOI: 10.1136/sti.2006.020545
|View full text |Cite
|
Sign up to set email alerts
|

The validity of self-reported likelihood of HIV infection among the general population in rural Malawi

Abstract: Self-reports of HIV infection were generally valid. Most invalid self-reports were due to overestimating the risk of having HIV. The implications of this finding are highlighted, as they pertain to the design of HIV prevention interventions and the expansion of HIV counselling, testing and treatment programmes in developing countries.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
28
2

Year Published

2008
2008
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 31 publications
(33 citation statements)
references
References 10 publications
3
28
2
Order By: Relevance
“…The slightly higher accuracy among females compared to males found in our study is a reversal of the findings of higher accuracy for males found in Malawi [15]. This difference in accuracy between males and females may be due to a higher overestimation of risk among males.…”
Section: Discussioncontrasting
confidence: 86%
See 1 more Smart Citation
“…The slightly higher accuracy among females compared to males found in our study is a reversal of the findings of higher accuracy for males found in Malawi [15]. This difference in accuracy between males and females may be due to a higher overestimation of risk among males.…”
Section: Discussioncontrasting
confidence: 86%
“…The level of accuracy of self-perceived risk (62%) found in this study, although lower than 71% reported in a Malawian study [15], is encouraging as accurate assessment of risk has been shown to be associated with good behaviours such as condom use in last sexual intercourse for example [18]. The slightly higher accuracy among females compared to males found in our study is a reversal of the findings of higher accuracy for males found in Malawi [15].…”
Section: Discussioncontrasting
confidence: 84%
“…The network data were collected by fi rst asking the respondents how many people in respondent's risk environment and vary with respondent's reports of risky behaviors. For instance, a study in rural Uganda found that patterns of HIV risk perception by age and gender mirrored actual seroprevalence patterns (Kengeya-Kayondo et al 1999), and Anglewicz and Kohler (2005) and Bignami-Van Assche, Chao, and Anglewicz (2005) showed that men's and women's assessments of risk are consistent with evidence that men's greatest risk is from extramarital partners and women's greatest risk is from their husbands.…”
Section: Data and Contextmentioning
confidence: 74%
“…However, it seems unlikely there would be differential reporting between the participants in the two models of testing. Furthermore, self-reported HIV status has been shown to have similar validity to other self-reported variables [25]. Lastly, the follow-up of patients at the HIV treatment clinic at the CHC where they were tested may not be an indication of an individual accessing care.…”
Section: Discussionmentioning
confidence: 99%